The importance of harmonizing working timetables in seaport clusters - Karmelić, Jakov; Tijan, Edvard (2018)
Seaport clusters are complex commercial systems, consisting of a large number of heterogeneous stakeholders. Therefore, it is important to harmonize their business procedures to ensure effectiveness. Harmonization implies the adjustment of differences and inconsistencies among different measurements, methods, procedures, schedules, specifications, or systems to make them uniform or mutually compatible. This paper will particularly research the inconsistencies of working timetables of various seaport cluster stakeholders, which hampers their business flow and seaport effectiveness in general. In order to analyse the inconsistencies of working hours of seaport cluster stakeholders, it was necessary to collect and summarize the working hours of various statutory authorities (government institutions) and service providers (private concessionaires) in the port of Rijeka, Croatia. Data was collected from 14 different stakeholders, and it was evident that working hours’ discrepancies exist, manifested by different and uneven periods of daily shifts, daily breaks and periods of regular and overtime work. Service providers have different shifts, and differently defined overtime (and overtime compensation). For the simplicity and transparency of seaport cluster operations, the authors recommend harmonizing the shifts, periods of regular and overtime work, and overtime compensation of all stakeholders, with the ultimate goal to increase the competitiveness of the seaport cluster and the traffic corridor as a whole.
Bibliografija: 5 jed.
Abstract.
Keywords: Morske luke -- Radno vrijeme -- Usklađivanje vremena -- Poslovni postupci -- Učinkovitost -- Klasteri; Rijeka -- Hrvatska